Economic potential of bioremediation using immobilized microalgae-based microbial fuel cells - Wu J.-Y.; Lay C.-H.; Chia S.R.; Chew K.W.; Show P.L.; Hsieh P.-H.; Chen C.-C. (Springer Science and Business Media Deutschland GmbH, 2023)
Algae; Biomass; Bioproducts; Bioremediation; Cost estimating; Cost reduction; Fertilizers; Microbial fuel cells; Microorganisms; Nutrients; Oxygen supply; Wastewater treatment; Water pollution; Cathodic reactions; Continuous energy; Current technology; Economic potentials; Electricity generation; Higher efficiency; Immobilized microalgae; Suspended anaerobic; Electric power generation